The Effect of Liquidity Ratio on the Company Financial Performance: Evidence from a Developing Economy - Hadi Jaaz, Adnan; Abdulhasan Jasim, Ali; Jafer Baqer, Issa; Abdullah Abbas, Yasir; Hasan Hadi, Asia (South Asian Journal of Social Sciences and Humanities, 2025)
This study purposes to analyze the link between liquidity ratios and the company financial  performance of companies in developing economy. It used secondary data from 118  companies from 2020 to 2024 by using Stata data analysis software. The study found a  important and positive association between liquidity ratios and company financial  performance. The connection is of great significance to financial managers, investors, and  policymakers, particularly in environments in the economy characterized by instability and  financial variability. It was found that firms that hold moderate liquidity lacking investing professionally may smart from a lower return on investment, representative that unnecessary liquidity can be main to ineffective utilization of capital. The study suggests that firms keep a suitable balance in liquidity ratios, enough to cover short-term requests without disrupting  utilization of existing funds for productive investments. Firms should grow continuing logical models to display liquidity depending on variations in the global and local economic  environment to confirm high financial flexibility. The findings of this paper help financial  managers make the best decisions concerning the best liquidity ratio, which balances  financial safety and investment in profitable changes. Good liquidity administration increases company financial performance by decreasing financing expenses or avoiding liquidity  issues.
Keywords: liquidity; company financial performance; developing economy